Peran Kader Kesehatan dalam Mendukung Program Pencegahan Penyakit Menular di Wilayah Kerja Puskesmas Batuyang Kabupaten Lombok Timur - Ikhsan, Muhammad (Gema Cendekia Institute, 2026)
Infectious diseases remain a significant public health concern in Indonesia, requiring comprehensive prevention strategies that involve community participation. Community health volunteers (health cadres) play a crucial role as intermediaries between health services and the community in implementing promotive and preventive health programs. This study aimed to analyze the role of health cadres in supporting infectious disease prevention programs in the working area of Batuyang Public Health Center, East Lombok Regency. This research employed a descriptive analytic design with a cross-sectional approach. The population consisted of all active health cadres in the Batuyang Public Health Center area, and a total sampling technique was used to recruit 60 respondents. Data were collected using a structured questionnaire that had been tested for validity and reliability. Data analysis was conducted using univariate analysis to describe respondent characteristics and bivariate analysis using the Chi-square test to examine the relationship between variables. The results showed that most health cadres had good knowledge regarding infectious disease prevention (65%), demonstrated positive attitudes toward prevention programs (70%), and actively participated in community health activities (68%). Statistical analysis indicated a significant relationship between cadres’ knowledge level and their role in infectious disease prevention activities (p < 0.05). These findings highlight that health cadres play an essential role in supporting infectious disease prevention programs at the community level. Strengthening the capacity of health cadres through continuous training and supervision is necessary to enhance the effectiveness of community-based health interventions.